Pengaruh Nilai Iklan Smartphone terhadap Niat Beli Produk - Wachid, Ainullah; Putra, Harmanda Berima (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study examines the influence of smartphone advertising value on product purchase intentions. This research uses quantitative methods by distributing online questionnaires to 151 Indonesian citizens without specific regional characteristics. The results of the analysis using regression analysis show that informativeness, entertainment and incentives are proven to have a positive effect on advertising value. Meanwhile, credibility and irritation were not proven to have a positive effect on advertising value. And finally, advertising value is also not proven to have a positive effect on purchase intention